2017
DOI: 10.1038/s41598-017-12157-1
|View full text |Cite
|
Sign up to set email alerts
|

Mucin 5B in saliva and serum of patients with oral lichen planus

Abstract: Oral lichen planus (OLP) is among the most common oral diseases. Its etiopathogenesis has yet to be clearly identified. OLP patients complain of mouth dryness. This study aimed to assess the level of Mucin 5B in OLP patients with xerostomia. This study was conducted on 30 OLP patients and 30 healthy individuals. In addition to patient complaint of mouth dryness, xerostomia was assessed by tongue blade and lipstick tests. Stimulated and unstimulated saliva were collected in plastic vials by spitting method. Lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…The unstimulated and stimulated saliva flow rates were significantly lower in OLP patients compared with controls, and the severity of xerostomia was significantly higher in OLP patients compared with controls. These findings, in line with the results of some previous studies, highlighted the presence of xerostomia and decreased salivary flow rate in OLP patients 5,8,21,22 . A previous study showed that altered composition of saliva (Mucin 5b) in OLP patients may lead to xerostomia 5 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The unstimulated and stimulated saliva flow rates were significantly lower in OLP patients compared with controls, and the severity of xerostomia was significantly higher in OLP patients compared with controls. These findings, in line with the results of some previous studies, highlighted the presence of xerostomia and decreased salivary flow rate in OLP patients 5,8,21,22 . A previous study showed that altered composition of saliva (Mucin 5b) in OLP patients may lead to xerostomia 5 …”
Section: Discussionsupporting
confidence: 92%
“…Another study assessed the level of salivary 5B mucin, which is responsible for moisture and lubrication of the oral cavity in OLP patients and healthy controls. The results showed that the level of salivary 5B mucin was significantly lower in OLP patients compared with healthy controls 5 . To better understand the pathogenesis of xerostomia in OLP, this study aimed to assess and compare the level of M3 muscarinic receptors in minor salivary glands of OLP patients and healthy controls.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In OLP, the patients with reticular or plaque-like forms tend to be asymptomatic [34] although atrophic and erosive lesions cause severe symptoms [29,38,39]. The main symptoms caused by the erosive, atrophic, and bullous forms in either OLP or lichenoid lesions include pain, soreness, and bleeding; the combination of these symptoms can affect the quality of life of the patients [4,18]. Dry mouth has been reported in LP patients [40].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Oral lichen planus (OLP) is a common chronic and recurrent immunologic inflammatory mucocutaneous disorder with unspecified etiology [1][2][3]. Recent data have attributed the etiopathogenesis to cell-mediated immune responses [4]. In contrast, lichenoid reactions are lesions with known etiology that may be clinically and histologically very similar to LP; this makes it difficult to differentiate these two entities [5][6][7].…”
Section: Introductionmentioning
confidence: 99%